The Urgency of the Bantul Regional Disaster Management Agency in Increasing Disaster Awareness among Women’s Community - Laras Lingganingrum; Sakir Sakir (ARISTO, 2024)
Women are included in the list of vulnerable victims of disaster due to their lack of skills and lower physical strength than men. The role of the Regional Disaster Management Agency (BPBD) as a communicator or messenger is required in the efforts to increase disaster awareness and information among women's community. This urgency is supported by the condition of the area which has a high risk of disaster as well as the fact that the total female population outnumbers the males. This research aims to find out how the BPBD of Bantul Regency uses social media to promote disaster awareness and information to the women's community. In the digital era, social media is considered capable of channeling messages more widely to reach underserved communities. This research used a qualitative method with a case study approach. The research results show that the BPBD of Bantul Regency have made some efforts to increase disaster awareness and information among women's community by involving direct participation. In carrying out the role, the communicator has a structured information delivery and processing chain by involving Pusdalops (the Operational Control Center) and teams from each field. This results in messages wrapped in the form of social media content, even though the disaster narrative does not yet represent efforts to increase disaster awareness and information for women's community. The target of this social media communication is the general public, both men and women. The existence of a structured information delivery and processing chain as well as mastered materials can make the messages reach the women's community. The researchers propose an alternative model for disaster communication through social media as an effort to increase disaster awareness and information among women's community without changing existing disaster information communication patterns. The researchers propose this model to fill the gap in the role of teams in each field who should have knowledge capacity related to the disaster awareness and information among women's community